PENGARUH PROFITABILITY, LEVERAGE, GROWTH OPPORTUNITY, NET WORKING CAPITAL TERHADAP CASH HOLDING - Rasyid, Rosmita; Devita, Christina (Jurnal Paradigma Akuntansi, 2025)
This study aims to obtain empirical evidence regarding the effect of profitability, leverage, growth opportunity, and net working capital on cash holding on consumer non cyclicals companies listed on the Indonesia Stock Exchange (IDX) for the period 2018-202. Sample was selected using purposive sampling method and the valid data was 43 companies. The technique that used in this research was multiple linear regression which is tested using SPSS IBM Statistics software version 29 and Microsoft Excel 2013. The result of this study showed that growth opportunity and net working capital have a significant and positive effect on cash holding, while profitability and leverage have no significant and negative effect on cash holding. The implication of this study is to consider growth opportunity and net working capital for optimazing company’s cash holding level.